Improving the Quality of Human Resources and the Welfare of Lecturers through Lecturer Certification : (A Literature Study and Direct Participation Observation) - Effiyaldi Effiyaldi; Syafril Syafril; Andi Makkulawu Panyiwi Kessi (Brilliant International Journal Of Management And Tourism, 2025)
This study aims to elaborate on improving the quality of human resources and the welfare of lecturers through a lecturer certification program. Lecturer certification is also very useful for the government in setting standards for lecturer qualifications in developing the Tri Dharma of Higher Education, namely Teaching, Research and Community Service. To achieve the goal of improving the quality of lecturers and improving the welfare of lecturers, lecturer certification is one of the most important ways in the higher education system in Indonesia. This study is an exploratory descriptive study with a Library study method and direct observation of the research problem. The results of the study indicate that lecturer certification allowances have a positive impact on improving the quality of lecturers and also improving the welfare of lecturers in increasing income for lecturers' living needs. It is hoped that this study can be a useful source of information for the government, the general public and other researchers in the future.